Women's solidarity economy initiatives to strengthen food security in response to disasters: Insights from two Philippine case studies. Issue 2 (4th April 2016) - Ofreneo, Rosalinda Pineda; Hega, Mylene D.
Abstract : Purpose: – The purpose of this paper is to present the knowledge gained from the experiences of community-based, women-led organizations of workers in the informal economy which strengthen food security, enhance livelihoods in peri-urban areas through solidarity economy initiatives, and advance women's empowerment as they respond to disasters arising from climate change. Design/methodology/approach: – This paper is based on case studies of Buklod Tao in San Mateo, Rizal, and the PATAMABA chapter in Sta. Barbara, Iloilo. The study was conducted within the tradition of gender-responsive participatory action research anchored on a human rights-based approach. Findings: – Experience of flooding motivated mature organizations of women informal workers to establish community-based peri-urban gardens connected to other solidarity-based sustainable livelihood initiatives to address food security concerns, increase income, and mitigate the impact of similar disasters. Although women have been empowered through these initiatives, much still has to be done to transform gender relations in various spheres. Research limitations/implications: – This research process lends itself toward unearthing gender inequalities which would otherwise remain hidden. Practical implications: – The solidarity-based initiatives documented in these case studies may be adopted by women informal workers' organizations in similar situations to advocate for and attain food security. Originality/value: – Solidarity-based strategies to attain food security among women informal workers are rarely documented for assessment and knowledge sharing. How they are or can be further empowered by these initiatives is a significant contribution to the literature on gender and disasters.